Transfer Pricing: Faktor-Faktor yang Mempengaruhi pada Perusahaan Pertambangan di BEI - Hendy Satria; Alamsyahbana, Muhammad Isa (Jurnal PROFITA : Akuntansi dan Manajemen, 2022)
This study aims to determine the factors that influence transfer pricing decisions in companies listed on the Indonesia Stock Exchange. The sample of this study was taken by purposive sampling by determining the criteria for mining companies listed on the Indonesia Stock Exchange during 2015-2018. Data analysis techniques used IBM SPSS version 24 software. The results of this study indicate that tax factors, Tunneling Incentive and Exchange Rate have a significant influence on the company's decision to carry out transfer pricing. In the determination coefficient test, it shows that tax, tunneling incentive, and exchange rate variables affect transfer pricing by 57.70%, while the remaining 43.3% is explained by other variables outside of the study.